Poverty dynamics and health in late childhood in the UK: evidence from the Millennium Cohort Study. Issue 11 (11th June 2019) - Lai, Eric T C; Wickham, Sophie; Law, Catherine; Whitehead, Margaret; Barr, Benjamin; Taylor-Robinson, David
Abstract : Objective: To assess the prevalence of different trajectories of exposure to child poverty and their association with three indicators of adolescent physical and mental health in UK children. Methods: We analysed data on 10 652 children from a large, prospective, nationally representative sample in the UK Millennium Cohort Study. The outcomes were mental health, measured by the Strengths and Difficulties Questionnaire (SDQ), physical health, measured by obesity and any longstanding illness, at age 14. The exposure was relative poverty (<60% of median of equivalised household income), measured at 9 months, 3, 5, 7, 11 and 14 years. Poverty trajectories were characterised using latent class analysis. ORs and 95% CIs were estimated using multivariable logistic regression, adjusted for maternal education and ethnicity. Results: Four poverty trajectories were identified: never in poverty (62.4%), poverty in early childhood (13.4%), poverty in late childhood (5.0%) and persistent poverty (19.4%). Compared with children who never experienced poverty, those in persistent poverty were at increased risk of mental health problems (SDQ score≥17 (adjusted OR (aOR): 3.17; 95% CI: 2.40 to 4.19)), obesity (aOR: 1.57; 95% CI: 1.20 to 2.04) and longstanding illness (aOR: 1.98; 95% CI: 1.55 to 2.52). Poverty in early childhood was related to higher risk of obesity than that in late childhood, while the opposite is observed for mental health problems and longstanding illness. Conclusions: Persistent poverty affects one in five children in the UK. Any exposure to poverty was associated with worse physical and mental health outcomes. Policies that reduce child poverty and its consequences are likely to improve health in adolescence.